Molecular Responses of Lactobacilli to Plant Phenolic Compounds: A Comparative Review of the Mechanisms Involved - Félix López de Felipe; Blanca de las Rivas; Rosario Muñoz (MDPI AG, 2021)
Lactobacilli are well-studied bacteria that can undergo oxidative selective pressures by plant phenolic compounds (PPCs) in plants, during some food fermentations or in the gastrointestinal tract of animals via dietary inputs. Lactobacilli are known to be more tolerant to PPCs than other bacterial groups and, therefore, must have mechanisms to cope with the effects of these metabolites. In this review, we intend to present what is currently known about the basics beyond the responses of Lactobacillus spp. to individual PPCs. We review the molecular mechanisms that are engaged in the PPC-modulated responses studied to date in these bacteria that have been mainly characterized by system-based strategies, and we discuss their differences and similarities. A wide variety of mechanisms are induced to increase the oxidative stress response highlighting the antimicrobial nature of PPCs. However other uncovered mechanisms that are involved in the response to these compounds are reviewed, including the capacity of PPCs to modulate the expression of molecular functions used by lactobacilli to adapt to host environments. This shows that these phytochemicals can act as more than just antimicrobial agents in the dual interaction with lactobacilli.